Evaluating earthen mortars for rendering - Santos, Tânia (2019)
As it is now recognized worldwide, the use of earth mortars for plastering and rendering is very important due to eco-efficiency. Rendering mortars have to present durability to rain water. A ready-mixed earth mortar based on natural clayish earth, siliceous sand and cut oat fibers was analyzed. In addition to this, three other mortars with volumetric proportion 1:3 (clayish earth: aggregate) were formulated in laboratory. A coarse and a fine sand were used as aggregate. Oat fibers were added to one of these mortars while oat fibers plus air lime were added to another. Microstructure, mechanical strength, capillary absorption, drying and mineralogical composition were evaluated. It was concluded that the addition of a small amount of air lime causes a decrease of mechanical strength and an increase on capillary absorption. For that reason it does not seem the best technique to increase durability for rendering mortars.